Content and form in the Rauf Parfi triads (Eurasian Journal of Humanities and Social Sciences, 2022)
For poetic speech, the dependence of content and form is important. In poetic discourse, the content is reflected in the idea reflected in it. (Four, Three, Five) Jehovah's Witnesses would be pleased to discuss these answers with you. We also encounter poems written in a variety of forms in the work of Ryan Perfufu